Special Protection for Perpetrators Underage Crimes Legal System International Criminal Law System - Lubis, Ade Rizky; Daming, Saharuddin; Purwaningsih, Prihatini (Universitas Ibn Khaldun Bogor, 2025)
This research discusses the special protection for underage offenders in the international criminal law system. The main focus of this study is how international legal instruments, such as the Convention on the Rights of the Child and the Beijing Rules, regulate such protection and its implementation in various countries. Using a normative legal research method with statutory, conceptual, and comparative approaches, this study analyzes the relevant legal rules and judicial practices. The results show that the international criminal law system emphasizes the principles of rehabilitation, diversion, and the prohibition of severe punishment for children. However, the implementation of these policies still varies, so legal harmonization and stricter supervision are needed. This research is expected to contribute to the strengthening of child protection policies in the criminal justice system and become a reference for policy makers to create a more humanist legal system. This research aims to analyze the special protection of underage offenders in the international criminal law system. Crimes committed by children have become an important concern in international law, especially after the recognition that children require greater protection due to their vulnerable status. The international criminal law system, which includes instruments such as the UN Convention on the Rights of the Child and the Statute of the International Criminal Court (ICC), regulates the protection of juvenile offenders. The study examines the implementation of child offender protection policies in several countries, including treaties, conventions and international court decisions. The results show that while the protection of juvenile offenders is widely provided for in international law, effective implementation is hampered by various challenges, including domestic policy incompatibilities and limited resources. Therefore, further efforts are needed to ensure more optimal implementation of protection for minor offenders at the international level.